2020
DOI: 10.17713/ajs.v49i5.1186
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Prediction of the Impact Factor of Journals Using Open-Access Databases

Abstract: This article is motivated by the work as editor-in-chief of the Austrian Journal of Statistics and contains detailed analyses about the impact of the Austrian Journal of Statistics. The impact of a journal is typically expressed by journal metrics indicators. One of the important ones, the journal impact factor is calculated from the Web of Science (WoS) database by Clarivate Analytics. It is known that newly established journals or journals without membership in big publishers often face difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although the study was designed for the regression of JIF values for a completed calendar year from which other bibliometric data is available as input features, it was shown that certain features have positive correlations with JIF and are useful when applied to a linear regression model. Another study has investigated the potential to estimate JIF values using machine learning approaches applied to bibliometric data from open-access databases Templ (2020). Such methods are motivated by the fact that for journals not indexed in SCI, the lack of public accessibility of the indexing database makes it impossible to calculate a journal's hypothetical JIF exactly as it would officially be done.…”
Section: Journal Predictionsmentioning
confidence: 99%
“…Although the study was designed for the regression of JIF values for a completed calendar year from which other bibliometric data is available as input features, it was shown that certain features have positive correlations with JIF and are useful when applied to a linear regression model. Another study has investigated the potential to estimate JIF values using machine learning approaches applied to bibliometric data from open-access databases Templ (2020). Such methods are motivated by the fact that for journals not indexed in SCI, the lack of public accessibility of the indexing database makes it impossible to calculate a journal's hypothetical JIF exactly as it would officially be done.…”
Section: Journal Predictionsmentioning
confidence: 99%
“…A similar study was performed by Brzezinski (2014). Templ (2020) predicted the IF using data from Google Scholar, ResearchGate, and Scopus. Through a statistical analysis, Huang et al (2019) demonstrated that modifying a journal's status to "Open Access" leads to a higher IF.…”
mentioning
confidence: 91%
“…A similar study was performed by Brzezinski (2014). Templ (2020) predicted the IF using data from Google Scholar, ResearchGate, and Scopus. Through a statistical analysis, Huang et al.…”
Section: Introductionmentioning
confidence: 99%